Landscape risk analysis of the 2003 Barkal-Rangamati (5.7 Mw) earthquake in Bangladesh using geospatial techniques and people’s perceptions - Biswajit Nath; Tania Sultana Shifa; Sumon Miah; Bo Zhong; Junjun Wu; Aixia Yang; Shukla Acharjee; Ramesh P. Singh (Geomatics, Natural Hazards & Risk)
Planning and urban sustainability depend equally on understanding land use and land cover (LULC) change, variability, and landscape risk (LR) assessment in earthquake-prone areas. This paper considered Barkal town and its environs (BTEN), an earthquake-prone area close to the 2003 Barkal-Rangamati Earthquake (5.7 Mw) for the LR change analysis from 2001–2024. Six different multi-temporal data for the years 2001, 2003, 2011, 2021, and 2024 are used for the detailed analysis to assess the spatial and temporal LULC and LR changes. Further, for LR mapping, Geographical Information System (GIS), and multi-criteria evaluation (MCE) based Analytical Hierarchy Process (AHP) approaches were used. The LR mapping of the study region was prepared using various tools and approaches of geospatial techniques i.e. lineament density (LD), LR analysis, the local geology, and the LULC of various timelines. Furthermore, the ROC-AUC curve considered to validate the LD image with the LR maps considered as a novel technique in this study. The LR in the earthquake-affected areas, people’s risk perception and surface and subsurface rupture estimation also found suitable in the present study. Our detailed results will ultimately help the planners to assess better the changing state of 2003 Barkal-Rangamati earthquake-prone areas in a sustainable manner.